Students' Understanding of Sharia Contracts: A Comprehensive Assessment of Translation, Interpretation, and Extrapolation Skills - Hidayat, Muh.; Ridwan, Muhammad; Jasri (Sekolah Tinggi Agama islam Negeri Majene, 2024)
The challenges in translation, interpretation, and extrapolation can result in a gap between students' theoretical knowledge of Sharia contract products and their ability to understand and apply them in practice, particularly in the context of Islamic finance. This research aims to assess the level of understanding of sharia contract products, focusing on three key aspects: translation, interpretation, and extrapolation. Using a survey approach, the study investigates how Sharia economic law students at Universitas Muhammadiyah Makassar comprehend Sharia contract products. The findings reveal that most students possess a satisfactory understanding of the subject matter, demonstrating a reasonably good ability to translate, interpret, and extrapolate the principles of sharia contracts. However, some students face challenges in fully grasping and applying these concepts, particularly in practical scenarios. A number of respondents exhibit a general understanding of Islamic financial institutions but lack the deeper capacity to translate and implement these concepts in real-world contexts.